2004
DOI: 10.1183/09031936.03.00059503
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of inspiratory muscle training in COPD patients: one year follow-up

Abstract: Maintenance of inspiratory muscle training in COPD patients: one year follow-up. P. Weiner, R. Magadle, M. Beckerman, M. Weiner, N. Berar-Yanay. #ERS Journals Ltd 2004. ABSTRACT: In most chronic obstructive pulmonary disease (COPD) patients, dyspnoea and functional exercise capacity may improve as a result of inspiratory muscle training (IMT). However, the long-term benefits of IMT have been investigated to a much lesser extent.The present study investigated the short-term and long-term benefits of IMT on insp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
63
0
13

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(79 citation statements)
references
References 27 publications
(26 reference statements)
3
63
0
13
Order By: Relevance
“…The load (or weight) of the valve can be adjusted to accommodate a wide range of starting abilities, as well as the rapid improvements in strength that accompany training. Increases in strength of 25-40% are achievable within 4-6 weeks [38,48,50,[53][54][55][56][57]. The training programme is simple, can be conducted in the patients' own home and with a minimal imposition upon their daily lives.…”
Section: A Practical Guide To Imtmentioning
confidence: 99%
See 1 more Smart Citation
“…The load (or weight) of the valve can be adjusted to accommodate a wide range of starting abilities, as well as the rapid improvements in strength that accompany training. Increases in strength of 25-40% are achievable within 4-6 weeks [38,48,50,[53][54][55][56][57]. The training programme is simple, can be conducted in the patients' own home and with a minimal imposition upon their daily lives.…”
Section: A Practical Guide To Imtmentioning
confidence: 99%
“…Successful outcomes of IMT have most commonly employed a technique of inspiratory muscle strength training known as pressure threshold training [29,38,48,50,[53][54][55][56]. In pressure threshold IMT the user breathes in against a spring-loaded valve.…”
Section: A Practical Guide To Imtmentioning
confidence: 99%
“…However, a meta-analysis by Salman et al 5) showed that IMT does not improve gait distance or respiratory d i s t r e s s . S u b s e q u e n t s t u d i e s h a v e s i n c e documented the efficacy of IMT [6][7][8][9][10][11] , and the American Thoracic Society and European Respiratory Society 2) issued a statement that, "IMT could be considered as adjunctive therapy in pulmonary rehabilitation, primarily with suspected or proven respiratory muscle weakness." Studies have shown that expiratory muscle training (EMT) increases maximal expiratory muscle pressure (PE max ), improves pulmonary function, ventilation function and exercise capability and alleviates respiratory distress caused by inspiratory load, activities of daily living or exercise in patients with COPD 12,13) , healthy individuals 10,[14][15][16][17][18][19] , multiple sclerosis (MS) patients [20][21][22] , myasthenia gravis (MG) patients 23) , neuromuscular disease (NMD) patients 24,25) , patients with tetraplegia caused by spinal cord injury 26,27) and Parkinson's disease patients 28,29) .…”
Section: Introductionmentioning
confidence: 99%
“…As the pressure-generating capacity of the respiratory muscles falls and as the ratio of the pressures produced by the respiratory muscles to the maximum pressure that can be achieved increases dyspnea progressively worsens [11]. Since there is an established association between respiratory muscle dysfunction and dyspnea, an improvement in respiratory muscle function with inspiratory muscle training (IMT) could lead to a reduction in dyspnea [12,13]. A meta-analysis of IMT in 17 clinical trials found limited support for its use in terms of improving pulmonary function, respiratory muscle strength and endurance, exercise capacity, and functional status in patients with COPD [14][15][16].…”
Section: Introductionmentioning
confidence: 99%